2012
DOI: 10.3358/shokueishi.53.57
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium Content in Foods with Aluminium-Containing Food Additives

Abstract: The aluminium (Al) content of 105 samples, including bakery products made with baking powder, agricultural products and seafoods treated with alum, was investigated. The amounts of Al detected were as follows (limit of quantification: 0.01 mg/g): 0.01-0.37 mg/g in 26 of 57 bakery products, 0.22-0.57 mg/g in 3 of 6 powder mixes, 0.01-0.05 mg/g in all three agricultural products examined, 0.03-0.90 mg/g in 4 of 6 seafood samples, 0.01-0.03 mg/g in 3 of 11 samples of instant noodles, 0.04-0.14 mg/g in 3 of 4 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The mean total daily dietary Al consumed by a 50-kg Japanese adult was 3.6 ± 1.3 mg/day (25.2 mg/week or 70 μg/kg-day) or approximately 25% of the 285 μg/kg-day PTWI (Benford et al 2012). Ogimoto et al (2012) conducted a similar survey and found that scones (0.37 mg/g), pound cake (0.36 mg/g), and salted jellyfish (0.90 mg/g) had the highest Al concentrations. Sato et al (2014) found the highest Al concentrations in processed Japanese confections (21.73 mg/kg) and the lowest in rice (0.32–0.43 mg/kg).…”
Section: Environmental and Occupational Exposurementioning
confidence: 99%
“…The mean total daily dietary Al consumed by a 50-kg Japanese adult was 3.6 ± 1.3 mg/day (25.2 mg/week or 70 μg/kg-day) or approximately 25% of the 285 μg/kg-day PTWI (Benford et al 2012). Ogimoto et al (2012) conducted a similar survey and found that scones (0.37 mg/g), pound cake (0.36 mg/g), and salted jellyfish (0.90 mg/g) had the highest Al concentrations. Sato et al (2014) found the highest Al concentrations in processed Japanese confections (21.73 mg/kg) and the lowest in rice (0.32–0.43 mg/kg).…”
Section: Environmental and Occupational Exposurementioning
confidence: 99%
“…Rehydrated JF show content of 92–96% water, 3–7% protein, and negligible carbohydrate, fat, and cholesterol levels ( 2 ). Calcium, magnesium, potassium, and sodium are the most present macro-elements, but once processed JF food products also contain elevated aluminum levels due to the alum curing agent ( 11 , 12 ). The long exposure of JF tissues to the curing agent, during processing, shipping, and storage, increases the salt penetration and tissue-binding of aluminum ions, resulting in a very high content of this metal.…”
Section: Introductionmentioning
confidence: 99%
“…Macro elements including calcium, magnesium, potassium, and sodium are high in fresh jellyfish tissues as their contents are affected by seawater; however, these elements are substantially reduced in edible jellyfish after desalting. While most salts can be removed by soaking in water, processed jellyfish contain elevated levels of aluminum due to the alum curing agent (Ogimoto et al 2012;Zhang et al 2016). The aluminum binds to the proteins in the gelatinous tissue, resulting in the desired crunchy and crispy texture.…”
Section: The Edible Productmentioning
confidence: 99%
“…Large quantities of effluent are generated as a byproduct of jellyfish processing, and need to be dealt with in a responsible way. Edible jellyfish may contain concerning amounts of aluminum (Wong et al 2010;Ogimoto et al 2012;Armani et al 2013;Zhang et al 2016), the consumption of which is linked to a number of negative health effects, including Alzheimer's disease (Perl and Brody 1980;Nayak 2002). The development of new processing technologies that either reduce the aluminum content in the edible products (e.g., Chen et al 2016) or eliminate the use of alum altogether is desirable (Hsieh and Rudloe 1994).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%